Theory and Practice of Mediation in Enggano Customary Law Community - Gayo, Sabela (International Asia Of Law and Money Laundering (IAML), 2025)
This study aims to examine the theory and practice of mediation in Enggano customary law community as a form of non-litigation dispute resolution mechanism rooted in local cultural values. The Enggano customary law community, which inhabits Enggano Island in Bengkulu province, has a unique social and legal system and is passed down through generations through oral traditions and communal practices. Adat mediation in Enggano is an integral part of the customary law system run by adat elders or community leaders who have moral authority in resolving various social issues, such as family conflicts, land disputes, to violations of customary norms. This study uses a normative legal approach with the support of qualitative data from literature studies and relevant anthropological documents, as well as analyzing how the adat mediation process takes place and what are its basic principles. In Enggano society, customary mediation prioritizes the value of deliberation, peace, and social rapprochement rather than formal condemnation. Thus, adat mediation is not only a dispute resolution tool, but also a mechanism for maintaining social cohesion and preserving local culture. However, in practice, Adat Enggano mediation is often faced with obstacles, especially when it comes to interacting with a more legalistic and formal national legal system. This study also explores the form of intersection between customary law and Indonesian national law, as well as how the two can complement each other in an effort to create a dispute resolution system that is contextual and responsive to the reality of Indigenous Peoples. The findings in this study indicate that, despite modernization and external pressures, adat mediation in Enggano still exists and has important value in the plural legal system in Indonesia.